Solitary neurofibroma of the gingiva with prominent differentiation of Meissner bodies : a case report - Okamura Kazuhiko; Ozasa Ryuki; Iwahashi Teruaki; Ohno Jun; Taniguchi Kunihisa (BMC, 2010)
Abstract Background Oral neurofibromas are peripheral nerve sheath tumors, similar to schwannomas. Histological variations in oral neurofibromas are relatively uncommon. Case presentation Here, we present a case of unique variation in the observed characteristics of a neurofibroma, with no relation to neurofibromatosis type-1 or von Recklinghausen disease of the skin. The neurofibroma was observed in the right mandibular gingiva of a 32-year-old Japanese woman. Histologically, it differed from conventional neurofibromas in that the tumor was composed of a mixture of fine fibrillary collagen in sheets and/or cords of neoplastic Schwann cells containing numerous clusters of Meissner bodies. Histologically, these bodies were in contact with neoplastic Schwann cells. The Meissner bodies were immunopositive for S-100 protein, neuron-specific enolase, and vimentin, but were negative for calretinin. CD34-positive spindle cells were observed around the Meissner bodies. No recurrence or signs of other tumors have been observed in the patient for 5 years after tumor resection. Conclusion To the best of our knowledge, no formal descriptions of sporadic, solitary neurofibromas containing numerous Meissner bodies occurring in the oral cavity are available in literature. We believe that an uncommon proliferation of Meissner bodies, as seen in the present case, may result from aberrant differentiation of neoplastic Schwann cells.